KEWARISAN ANAK LUAR KAWIN (STUDI ATAS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010) - Lubis, Ihsan Helmi (Al-Mazaahib: Jurnal Perbandingan Hukum, 2017)
The issue of Constitutional Court Decision Number 46/PUU-VIII/2010 concerning the status of children outside of marriage has a great influence on the laws and regulations in Indonesia, especially the Marriage Law. The substance of this Constitutional Court ruling changed the category of legitimate children as understood by applicable law as well as Islamic law. An outsider who has been considered an illegitimate child, based on the decision of the Constitutional Court is categorized as a legitimate child, thus having a civic relationship with his biological father. This article explains the implications of the decision of the Constitutional Court's Decision, especially in relation to the civil rights of its inheritance. The focus of the discussion on two things, namely how the inheritance of children outside of marriage and how the view of Islamic law on his inheritance. The results of this study reveal two things. First, after the Decision of the Constitutional Court Number 46/PUU-VIII /2010, an outsider or child born of sirri marriage or not being registered shall be entitled to inheritance, if it has been justified by the Court. Between father and son have a blood relationship and the child is classified as a legitimate child. Second, the inheritance of children outside marriage or who are born of sirri marriage or not registered can only be done through a will. This is because the child can only be attributed to his mother and is not counted as the heir of his father.